THE EFFECT OF COMPENSATION, LEADERSHIP STYLE AND WORK DISCIPLINE ON THE PERFORMANCE OF HOSPITAL EMPLOYEE IN UNITED STATES - Andres Rodriguez-Clare; Jonathan Dingel (PT. Radja Intercontinental Publishing, 2021)
This study aims to find out how InfluenceCompensation, Leadership Style and Work Discipline on the Performance of Hospital Employee In United States. Therefore the author is interested in taking the title